Enhanced conflict monitoring via a short-duration, video-assisted deep breathing in healthy young adults: an event-related potential approach through the Go/NoGo paradigm - Cheng, Kok Suen; Chang, Yun Fah; Han, Ray P.S.; Lee, Poh Foong (PeerJ (San Francisco, CA), 2017)
Practitioners of mindfulness are reported to have greater cognitive control especially in conflict monitoring, response inhibition and sustained attention. However, due to the various existing methods in each mindfulness practices and also, the high commitment factor, a barrier still exists for an individual to pick up the practices. Therefore, the effect of short duration deep breathing on the cognitive control is investigated here. Short duration guided deep breathing videos consisting of 5, 7 and 9 min respectively were created and used on subjects training. The effect on cognitive control was assessed using a Go/NoGo task along with event-related potential (ERP) measurements at Fz, Cz, and Pz. From the study, the significant outcome showed at the follow-up session in which participants engaged for 5 min deep breathing group showed a profound NoGo N2 amplitude increment as compared to the control group, indicating an enhanced conflict monitoring ability. An inverse relationship between the NoGo N2 amplitude and the breathing duration is observed as well at the follow-up session. These results indicated the possibility of performing short duration deep breathing guided by a video to achieve an enhanced conflict monitoring as an alternative to other mindfulness practices and 5 min is found to be the optimum practice duration. This study is the first to establish a relationship between deep breathing and conflict monitoring through ERP. The study population of young adults taken from the same environment reduces the variance in ERP results due to age and environment. A larger sample size would provide a greater statistical power. A longer duration of deep breathing should be investigated to further clarify the relationship between the practice duration and the NoGo N2 amplitude. The result can be split by gender and analyzed separately due to the different brain structure of males and females.